Who are the tsahars and the peculiarities of good wishes for the yurt - (SUYILASIQIN) Soyoltsetsen (Nomadic Civilization: Historical Research)
In the 21st century, when the wave of globalization gained momentum, there were huge changes in the social, political, economic and intellectual life of the country, especially the social ecology of the nomadic culture or the external environment changed and evolved, the mutual respect for tradition and innovation was lost, and the traditional behavior of Mongols tended to be forgotten. This is actually a question of the existence or non-existence of the culture. Therefore, it is necessary to carefully study wedding rituals, which are a complete complex of Mongolian cultural rituals, and to develop methods for promoting and popularizing useful and advanced customs that are compatible with today’s life, and for children and youth to master them from an early age. In particular, it is a meaningful ceremony that symbolizes the good future of the family, which is the foundation of the state, and makes people understand the meaning of the family, and makes them feel the responsibility. The wedding ceremony of the Tzahar ethnic group is specially studied. It is interesting how the genre of poetry has been passed down and how it has changed in the present day. The reasons and factors that led to change have been discussed in this article on the example of home blessing.